IMPLEMENTASI RUMPON RAMAH LINGKUNGAN (BIODEGRADABLE FAD) SEBAGAI SOLUSI EKOLOGIS PADA PERIKANAN TUNA - Haruna Haruna; Simon Tubalawony; Agustinus Tupamahu; Kedswin Gerson Hehanussa (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Tanjung Air Panas Hamlet, Tulehu Village, is one of the traditional tuna fisheries centers using hand line fishing gear located on the eastern coast of Ambon Island. In fishing practices, local fishers utilize conventional fish aggregating devices (FADs), which are mostly made of synthetic materials such as plastic and nylon nets. The use of these materials has the potential to contribute to marine pollution and is less supportive of sustainable marine ecosystem management. This community service activity aimed to introduce and implement environmentally friendly fish aggregating devices (biodegradable FADs) made from locally available natural materials such as bamboo, coconut leaves, and rattan. The implementation methods included socialization, training on FAD construction, technical assistance, and evaluation using a Likert-scale questionnaire to assess fishers’ level of understanding, technical skills, and attitudes toward the introduced technology. The activity involved two groups of tuna hand line fishers with a total of 25 participants who took part in the entire program. The evaluation results showed that the average scores of the indicators ranged from 4.1 to 4.8 (good to very good category). Fishers’ understanding of the concept of environmentally friendly FADs obtained an average score of 4.6, technical skills in assembling and installing FADs ranged from 4.2 to 4.3, and fishers’ willingness to shift from synthetic-material FADs to natural-material FADs obtained a score of 4.7. These results indicate a positive response from fishers toward the implementation of environmentally friendly FADs, particularly in terms of knowledge, technical skills, and ecological commitment. The application of biodegradable FADs has the potential to serve as an environmentally friendly fishing technology alternative and support sustainable tuna fisheries management in Tulehu waters.